Pemerkosaan dalam Perkawinan (Analisis Undang-Undang No. 1 Tahun 2023 pada Pasal 473 KUHP dalam Tinjauan Hukum Islam): Rape within Marriage (Analysis of Law No. 1 of 2023 on Article 473 of the Criminal Code in Islamic Law Review) - Muhammad Taufan Djafri; Abdul Munawir; Muzammil, Muzammil (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The aim of this research is to examine how Indonesian positive law and Islamic law view and handle cases of marital rape. The research methodology used is descriptive qualitative with a normative, philosophical and comparative approach. Data was collected through literature review from relevant primary and secondary sources. The research results found are as follows: first, Indonesian positive law will provide a maximum sentence of 12 (twelve) years for perpetrators of marital rape, if the victim reports it to the authorities. Second, according to Islamic law, this problem is divided into 2 parts as follows: it is not permissible, this has been agreed upon by the ulama when a husband forces his wife to have intercourse through the anus, during menstruation, fasting (fardhu), pilgrimage, not having paid kafarat, due to illness. severe, old age which can endanger the wife and when the husband has not fulfilled the muajjala dowry. Yes, the ulama have also agreed that a husband may force his wife to have sex if her condition is capable of serving him. Third, this analysis shows that there is harmony in several aspects between Islamic law and Indonesian positive law in dealing with marital rape. However, in several cases, Indonesian positive law is considered inadequate in protecting the rights of husbands accused of coercion against their wives. Meanwhile, from the perspective of Islamic law, a husband has the right to force his wife as long as the wife's condition allows her to serve her husband. It is hoped that the implications of this research will become a reference for creating more comprehensive legal adjustments and harmonization to ensure justice and balanced protection for all parties involved.